2017
DOI: 10.1073/pnas.1712946114
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomics identifies STEAP4 as a critical regulator of mitochondrial dysfunction linking inflammation and colon cancer

Abstract: Inflammatory bowel disease (IBD) is a chronic inflammatory disorder and is a major risk factor for colorectal cancer (CRC). Hypoxia is a feature of IBD and modulates cellular and mitochondrial metabolism. However, the role of hypoxic metabolism in IBD is unclear. Because mitochondrial dysfunction is an early hallmark of hypoxia and inflammation, an unbiased proteomics approach was used to assess the mitochondria in a mouse model of colitis. Through this analysis, we identified a ferrireductase: six-transmembra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 46 publications
(46 reference statements)
2
80
0
Order By: Relevance
“…Next, we sought to determine whether IL-17-induced STEAP4mediated cellular copper uptake contributes to colon cancer progression in human. Consistent with a previous report 46 , we found that STEAP4 was overexpressed in a subset of human colon cancer tissues and correlated with worse prognosis for human CRC ( Fig. 6a and Supplementary Fig.…”
Section: Steap4 Promotes Colitis-associated Colon Tumorigenesissupporting
confidence: 93%
See 1 more Smart Citation
“…Next, we sought to determine whether IL-17-induced STEAP4mediated cellular copper uptake contributes to colon cancer progression in human. Consistent with a previous report 46 , we found that STEAP4 was overexpressed in a subset of human colon cancer tissues and correlated with worse prognosis for human CRC ( Fig. 6a and Supplementary Fig.…”
Section: Steap4 Promotes Colitis-associated Colon Tumorigenesissupporting
confidence: 93%
“…Although the metallo-reductase activity of STEAP4 has been extensively characterized in vitro [29][30][31] , the pathophysiological function of STEAP4 has remained elusive. A recent study from Xue et al 46 has shown that STEAP4 overexpression in colonic epithelia cells increased the amount of iron in mitochondria at steady state and rendered mice susceptible to chemically induced colitis and colon tumorigenesis. By employing a loss-of-function approach, we found that both copper and iron accumulation were impaired in the colonic epithelial cell-specific STEAP4-deficient mice during the process of colon tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Mice treated with dextran sodium sulfate (DSS) to induce colitis exhibited swollen mitochondria, increased mtROS generation, decreased ETC activity and ATP level in the colonic mucosa that was ameliorated by anti-TNFα treatment. 54,64 Mice with deletion of IRGM, a CD susceptibility gene that affects mitochondrial fission and induces autophagy, exhibited increased susceptibility to experimental colitis. 65,66 Polymorphisms in SLC22A5, which encodes OCTN2 the carnitine transporter involved in mitochondrial FAO, are associated with CD risk.…”
Section: Mitochondrial Dysfunction and Inflammatory Bowel Diseasesmentioning
confidence: 99%
“…Sections were then post-fixed with 1% OsO 4 (Sigma-Aldrich) for 1 h and embedded in resin. Ultra-thin sections (70 nm) in each group were prepared and stained as previous description 29 . The structures of colonic sections were observed using TEM (Philips Tecnai 20 U-Twin, Holland).…”
Section: Transmission Electron Microscopy (Tem) and Morphometrymentioning
confidence: 99%